Estereotipo psico-cultural de la menopausia en mujeres peruanas: estudio piloto en San Juan de Lurigancho- Lima - Dulanto, Rosa (2024)
Objective: To define the stereotype conditions (perceptions, knowledge and attitudes) of menopause among women between 40 and 55 years old, pertaining to the urban outskirts side of Lima. Material and methods: A qualitative and quantitative study was carried out, with 38 women of 40-55 years old from San Juan de Lurigancho. We used surveys and focus groups to establish their feelings related to menopause such us, attitude, expectations and symptomatology. Results: Menopause was considered a natural, biological and psychological change, it which preceded old age and initiated infertility. It was considered a relief to some and a frustation to others. Others meanings were illnesses with possible solutions as self-control, psychological support and/or medical assistance, release of home responsibilities and major social acceptance. The attitude towards the menopause reflected a strong desire to leave home, fear of more diseases and end to the disadvantages of becoming pregnant. Among the most-related symptoms to menopause were "aches and pains", behavioral changes, flushing and fatigue. Attitude towards sexuality included lack of changes, either sexual reawakening or disappearance of sexual desire with need for affection in both cases though not of sexual contact. Acceptance to hormone replacement treatment was variable. Conclusion: This study revealed a partial ignorance of the menopause and almost total ignorance of HRT, with predominant negative attitude, but, with a positive attitude towards authenthic accesible information on the subject.